ATRX loss refines the classification of anaplastic gliomas and identifies a subgroup of IDH mutant astrocytic tumors with better prognosis - Wiestler, Benedikt; Capper, David; Holland-Letz, Tim; Korshunov, Andrey; Deimling, Andreas von; Pfister, Stefan; Platten, Michael; Weller, Michael; Wick, Wolfgang (Acta neuropathologica, 2013)
Mutation/loss of alpha-thalassemia/mental retardation syndrome X-linked (ATRX) expression has been described in anaplastic gliomas. The present study explored the role of ATRX status in the molecular classification of anaplastic gliomas and its impact on survival in the biomarker cohort of the NOA-04 anaplastic glioma trial. Patients (n = 133) of the NOA-04 trial were analyzed for ATRX expression using immunohistochemistry. ATRX status was correlated with age, histology, isocitrate dehydrogenase (IDH), 1p/19q, alternative lengthening of telomeres (ALT) and O6-methylguanine-DNA methyltransferase (MGMT) status, and the trial efficacy endpoints. Loss of ATRX expression was detected in 45 % of anaplastic astrocytomas (AA), 27 % of anaplastic oligoastrocytomas (AOA) and 10 % of anaplastic oligodendrogliomas (AO). It was mostly restricted to IDH mutant tumors and almost mutually exclusive with 1p/19q co-deletion. The ALT phenotype was significantly correlated with ATRX loss. ATRX and 1p/19q status were used to re-classify AOA: AOA harboring ATRX loss shared a similar clinical course with AA, whereas AOA carrying 1p/19q co-deletion shared a similar course with AO. Accordingly, in a Cox regression model including ATRX and 1p/19q status, histology was no longer significantly associated with time to treatment failure. Survival analysis showed a marked separation of IDH mutant astrocytic tumors into two groups based on ATRX status: tumors with ATRX loss had a significantly better prognosis (median time to treatment failure 55.6 vs. 31.8 months, p = 0.0168, log rank test). ATRX status helps better define the clinically and morphologically mixed group of AOA, since ATRX loss is a hallmark of astrocytic tumors. Furthermore, ATRX loss defines a subgroup of astrocytic tumors with a favorable prognosis.
Gesehen am 08.11.2021